Disseminating Agricultural Research Information: A case study of farmers in Mlolo, Lupalama and Wenda villages in Iringa district, Tanzania - Mubofu, Christian; Elia, Emmanuel (University of Dar es Salaam Library Journal, 2018)
This study investigated the extent to which agricultural research information is disseminated to farmers. It was conducted in 2015 at Mlolo, Lupalama and Wenda villages of Iringa district. Data were collected from 90 farmers using questionnaires, in-depth interviews and focus group discussions. The study established that the extent of disseminating agricultural research information to farmers was low. The main types of agricultural research information disseminated to farmers included information on improved seed varieties, information on the use of fertilisers, information on crop management and information on pest management. On the hand, the barriers to farmers ' access to agricultural research information included inadequate numbers of extension officers, inadequate funding, inadequate sources of information, non-availability of electricity, political interference and the absence of information centres. On the basis of these findings, the study calls for joint efforts aimed to increase the timely dissemination of agro-information to the farmers. In addition, there is a need to use researchers, religious leaders, and community-based organisations as key dissemination pathways to disseminate such information. The study further recommends for the need to repackage agricultural research information tailored towards meeting the farmers ' needs. Furthermore, the study urges the government to recruit more extension officers and station them in rural areas. Also, improving access to electricity in villages, allocation of more funds to agro-sector, prohibiting political interference in professional jobs and establishment of community based information centres could improve the availability, access to and use of agricultural research information.